Flocculation Treatment for Mitigating Clogging of Dredge Slurry Under Vacuum Preloading with Particle Image Velocimetry Analysis - Jingling Lu; Xuexing Zhang; Zhengxian Yang; Shanlin Xu (Applied Sciences)
To examine the effect of flocculation treatment on slurry clogging during vacuum preloading, this study conducted vacuum preloading model tests using lime, anionic polyacrylamide (APAM), and the dual use of polyaluminum chloride (PAC) and APAM in conjunction with particle image velocimetry (PIV) analysis. The results demonstrated that flocculation treatment enhanced the efficiency of vacuum preloading and mitigated the clogging of slurry. Compared to untreated slurry, the lime-flocculated slurry exhibited an approximately 248% increase in pore water pressure dissipation, a 462% increase in clogging zone width, and an 80% improvement in slurry strength near the PVD. The dual use of PAC and APAM significantly improved the slurry’s filtration performance by approximately 77 s, resulting in the highest water discharge rate (47% higher than untreated slurry) under vacuum pressure. In contrast, APAM alone enhanced the water discharge rate primarily in the early stages of vacuum preloading but had a limited effect on the final water discharge volume and horizontal strain. Furthermore, this study investigated the evolution of the clogging zone in flocculated slurry and elucidated the underlying mechanism of flocculation in mitigating the clogging of slurry. The findings can provide a theoretical basis for the selection of flocculants and the arrangement of PVDs in large-scale land reclamation and dredged slurry treatment projects.